Overexpression of survival motor neuron improves neuromuscular function and motor neuron survival in mutant SOD1 mice - Turner, B; Turner, B; Alfazema, N; Sheean, R; Sheean, R; Sleigh, J; Sleigh, J; Davies, K; Horne, M; Horne, M; Talbot, K; Talbot, K (2014)
Spinal muscular atrophy results from diminished levels of survival motor neuron (SMN) protein in spinal motor neurons. Low levels of SMN also occur in models of amyotrophic lateral sclerosis (ALS) caused by mutant superoxide dismutase 1 (SOD1) and genetic reduction of SMN levels exacerbates the phenotype of transgenic SOD1G93A mice. Here, we demonstrate that SMN protein is significantly reduced in the spinal cords of patients with sporadic ALS. To test the potential of SMN as a modifier of ALS, we overexpressed SMN in 2 different strains of SOD1G93A mice. Neuronal overexpression of SMN significantly preserved locomotor function, rescued motor neurons, and attenuated astrogliosis in spinal cords of SOD1G93A mice. Despite this, survival was not prolonged, most likely resulting from SMN mislocalization and depletion of gems in motor neurons of symptomatic mice. Our results reveal that SMN upregulation slows locomotor deficit onset and motor neuron loss in this mouse model of ALS. However, disruption of SMN nuclear complexes by high levels of mutant SOD1, even in the presence of SMN overexpression, might limit its survival promoting effects in this specific mouse model. Studies in emerging mouse models of ALS are therefore warranted to further explore the potential of SMN as a modifier of ALS. © 2014 Elsevier Inc.